Catalysing sustainable solutions to the growing climate crisis [CGIAR-UNHCR] - Läderach, Peter R.D.; Craparo, Alessandro Carmelo William; Taiwo, Ibukun (CGIAR System Organization, 2023)
CGIAR FOCUS Climate Security group, under its CGIAR Initiative on Climate Resilience (ClimBeR), and the CGIAR Initiative on Fragility, Conflict, and Migration, are collaborating to provide critical insights for UNHCR's Strategic Global Framework for Climate Action. Using "tailored hazard indices" to evaluate climate-related risks specifically affecting displaced individuals being supported by UNHCR, their efforts have yielded significant insights and valuable guidance to inform UNHCR's initiatives leading up to 2030.